2013
DOI: 10.1007/s10900-013-9697-6
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus-Mediated Cervical Cancer Awareness and Gardasil Vaccination: A Pilot Survey Among North Indian Women

Abstract: Human Papillomavirus (HPV)-mediated cervical cancer is a leading cause of morbidity and mortality in women worldwide, including Indian women. Cervical cancer control and prevention strategies are being adopted in developing nations to reduce the increasing burden of HPV infection in the vaccine era. The present study, therefore, aimed to evaluate cervical cancer awareness and knowledge of Gardasil vaccination in North Indian women. A pilot survey was conducted among 103 women of North Indian ethnicity residing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In a study by Pandey and Chandravati21 from Lucknow, cervical cancer awareness and knowledge of Gardasil ® vaccination were evaluated among north Indian women and 28.1 per cent awareness was reported for this HPV vaccine. Another cross-sectional study among the medical students of a tertiary care hospital in Delhi reported that 18 per cent of them did not know that HPV vaccination prevented cervical cancer and 50 per cent thought that vaccination induced false sense of security22.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Pandey and Chandravati21 from Lucknow, cervical cancer awareness and knowledge of Gardasil ® vaccination were evaluated among north Indian women and 28.1 per cent awareness was reported for this HPV vaccine. Another cross-sectional study among the medical students of a tertiary care hospital in Delhi reported that 18 per cent of them did not know that HPV vaccination prevented cervical cancer and 50 per cent thought that vaccination induced false sense of security22.…”
Section: Discussionmentioning
confidence: 99%
“…The cervical cancer susceptibility can be affected mainly by HPV infection and varied with some other factors, such as HPV awareness and toll-like receptor gene polymorphisms (7)(8)(9). It was reported that due to the nation, socioeconomic status, age, ethnicity, and geographic location of populations were different, the HPV prevalence was substantially varied with different populations (10,11), and the HPV genotype distribution also differed in various regions worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 77 papers and one dissertation were eligible for analysis and were listed in the order of publication years. [171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364656667686970717273747576777879808182838485868788899091929394] The review process is explained in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The studies consist of different populations such as women and men from different community groups[17202425313235394143454751616669717379808586909293]And attended clinics[2729425259676872757682]Students (nursing/medical/paramedical/nonmedical)[3840464850565860646974818389]Health-care providers (doctors, nurses, and other health workers);[1828365354555657626365667778889194] migrated Indians;[1921262730333437498487] and cervical cancer patients. [23]…”
Section: Methodsmentioning
confidence: 99%